Online impedance spectroscopy estimation of a dc–dc converter connected battery using a switched capacitor‐based balancing circuit. Issue 7 (10th July 2019) - Varnosfaderani, Mina Abedi; Strickland, Dani
Abstract : This study investigates a novel method of undertaking online electrochemical impedance spectroscopy measurements to estimate battery impedance across the frequency range using a battery balancing circuit. A switched capacitor balancing system is used to generate an excitation signal of low‐frequency of variable values from which battery voltage and current can be measured to estimate the impedance.